TINJAUAN TERHADAP PELAKSANAAN PENAGIHAN PAJAK BUMI DAN BANGUNAN YANG TERHUTANG OLEH BADAN PENDAPATAN DAERAH BERDASARKAN PERATURAN DAERAH KOTA SAMARINDA NOMOR 04 TAHUN 2011 TENTANG PAJAK DAERAH - Zalukhu, Utu Selama (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTLand and builing (PBB) tax collection is done ever year if the tax return is payable, receiver by the tax payer, the regional income month deler mines the done dot cof payment and tax patment is no later than 30 (thirty) working days after the time the tax becomos due and the maxsimum is 6 ( six) months the since the dote of receipt of SPPT by the tax payer SPPT, i cal tax assesment latter (SKPD) underpaid underpayment local tax assessment latter (SKPDKBT), local tax bill (STPD), correcti letter, and appeal decision which causes the amount of tax to be paid to increase is the basis tax collection and must be paid a maxsimum  period of one (1) month from the date of Issue.         Samarinda city regional regulation number 04 of 2011 concerning local taxes, arbicle 74 paragraph 2 (two) is carried out based regulation law number 19 year 1997 as amended by law number 19 year 2000 regarding tax collection can be gruaped into 2 (two), namely, passive billing and active billing.Keywords : Tax collection due